Increased expression and plasma levels of myeloperoxidase are closely related to the presence of angiographically-detected complex lesion morphology in unstable angina. Issue 21 (18th October 2010) - Naruko, T; Furukawa, A; Yunoki, K; Komatsu, R; Nakagawa, M; Matsumura, Y; Shirai, N; Sugioka, K; Takagi, M; Hozumi, T; Itoh, A; Haze, K; et al.
Abstract : Background: Myeloperoxidase (MPO) is a leucocyte enzyme that catalyses the formation of a number of reactive oxidant species. Objective: The purpose of this study is to evaluate the relationship between angiographic coronary plaque morphology in patients with unstable angina pectoris (UAP) or stable angina pectoris (SAP) and MPO levels. Patients and design: Plasma MPO levels on admission were measured in 236 patients with UAP, 146 with SAP and 85 control subjects using an ELISA kit. The angiographic morphology of the culprit lesion was classified into two types, simple or complex, based on the Ambrose classification. In addition, 61 atherectomy specimens obtained from a different cohort of patients with UAP and SAP were studied immunohistochemically for MPO. Results: Median (IQR) plasma MPO levels in patients with UAP with a complex lesion were significantly higher than in patients with a simple lesion (41.9 (21.7–73.7) ng/ml vs 20.5 (15.9–27.9) ng/ml, p<0.0001), but there was no significant difference between the two groups in patients with SAP. On multivariate analysis, raised plasma MPO levels and Braunwald class III were independent factors for angiographically-detected complex lesions (adjusted OR 12.49, 95% CI 3.24 to 48.17, p=0.0002). In the atherectomy specimens the number of MPO-positive cells in patients with UAP with complex lesions was significantly higher (p<0.0005) than in patients with simple lesions. Moreover, in this cohort, plasma MPO levels were positively correlated with the number of MPO-positive cells in atherectomy specimens (R=0.42, p=0.024). Conclusions: This study shows that increased expression and plasma MPO levels are closely related to the presence of angiographically-detected complex lesion morphology in patients with UAP.